Biventrikulární stimulace vs.stimulace z hrotu pravé komory - Yu, C. M (Clinical Cardiology Alert, 2010)
Observational studies suggest that conventional right ventricular apical pacing may have a deleterious effect on left ventricular function. In this study, we examined whether biventricular pacing is superior to right ventricular apical pacing in preventing deterioration of left ventricular systolic function and cardiac remodeling in patients with bradycardia and a normal ejection fraction. METHODS: In this prospective, double-blind, multicenter study, we randomly assigned 177 patients in whom a biventricular pacemaker had been successfully implanted to receive biventricular pacing (89 patients) or right ventricular apical pacing (88 patients). The primary end points were the left ventricular ejection fraction and left ventricular end-systolic volume at 12 months. RESULTS: At 12 months, the mean left ventricular ejection fraction was significantly lower in the right-ventricular-pacing group than in the biventricular-pacing group (54.8+/-9.1% vs. 62.2+/-7.0%, P<0.001), with an absolute difference of 7.4 percentage points, whereas the left ventricular end-systolic volume was significantly higher in the right-ventricular-pacing group than in the biventricular-pacing group (35.7+/-16.3 ml vs. 27.6+/-10.4 ml, P<0.001), with a relative difference between the groups in the change from baseline of 25% (P<0.001). The deleterious effect of right ventricular apical pacing occurred in prespecified subgroups, including patients with and patients without preexisting left ventricular diastolic dysfunction. Eight patients in the right-ventricular-pacing group (9%) and one in the biventricular-pacing group (1%) had ejection fractions of less than 45% (P=0.02). There was one death in the right-ventricular-pacing group, and six patients in the right-ventricular-pacing group and five in the biventricular-pacing group were hospitalized for heart failure (P=0.74). CONCLUSIONS: In patients with normal systolic function, conventional right ventricular apical pacing resulted in adverse left ventricular remodeling and in a reduction in the left ventricular ejection fraction; these effects were prevented by biventricular pacing. (Centre for Clinical Trials number, CUHK_CCT00037.) 2009 Massachusetts Medical Society
Keywords: Pacemaker, Artificial; financování organizované; Randomized Controlled Trials as Topic; Stroke Volume; Female; Atrioventricular Block; dysfunkce levé srdeční komory; Quality of Life; ženské pohlaví; Ventricular Dysfunction, Left; atrioventrikulární blokáda; echokardiografie trojrozměrná; kvalita života; funkce levé komory srdeční; lidé; dvojitá slepá metoda; Sick Sinus Syndrome; Cardiac Volume; Ventricular Remodeling; Echocardiography, Three-Dimensional; Financing, Organized; prospektivní studie; Double-Blind Method; syndrom chorého sinu; Male; Aged; Prospective Studies; tepový objem; remodelace komor; randomizované kontrolované studie jako téma; kardiostimulátor; objem srdce; senioři; mužské pohlaví; Bradycardia; bradykardie; Ventricular Function, Left; Humans